A Remote Monitoring and Maintenance System for Industrial Robots. Issue 1 (1st November 2022) - Zhou, Jian; Ding, Xiao-jian; Sun, Li-Jun; Yang, Yun-Fan; Wang, Yuan-hang; Liu, Wen-Wei
Abstract: Technologies such as external sensors, data acquisition, trend analysis, and cloud services make remote operation and maintenance of equipment status monitoring more convenient and lower maintenance costs. In this paper, an industrial robot operation and maintenance system is designed. First, the online monitoring of the robot is realized by collecting the control parameters, state parameters, fault information and external sensor monitoring information of the industrial robot. Then, the health baseline of the industrial robot is established based on the historical operation data. The online data is compared with the baseline data to realize the online assessment of the robot's health status. Finally, a visualization platform for remote operation and maintenance of the robot is built to realize the online display of parameters, health trend tracking and fault status early warning, which is convenient for maintenance personnel to take timely countermeasures.